Cangrelor Bridging Within 6 Months of a Drug-Eluting Stent in a Patient for Emergency Cervical Spine Surgery: A Case Report. Issue 2 (15th July 2019) - Hu, Tiffany Y.; Peeters, Sophie M.; Nagasawa, Daniel T.; Kamdar, Nirav V.; Brook, Rachel P.; Sun, Jesse; Park, Sandy; Moreland, Natalie C.; Cruz, Daniel; Macyszyn, Luke; Press, Marcella Calfon
Abstract : The recommended duration of dual antiplatelet therapy after drug-eluting stent placement presents a dilemma for patients with recent stenting who require urgent or emergency noncardiac surgery. We present the case of a patient with recent drug-eluting stent placement (<6 months) on dual antiplatelet therapy who underwent successful emergency cervical spine surgery with antiplatelet therapy bridged using cangrelor, an intravenous P2Y12 inhibitor antiplatelet agent. Our experience illustrates the multidisciplinary approach to a patient with high thrombotic and bleeding risk who underwent neurosurgery off both aspirin and a P2Y12 inhibitor.